2019
DOI: 10.17159/0379-4350/2019/v72a34
|View full text |Cite
|
Sign up to set email alerts
|

Kinetics, Thermodynamics and Isothermal Modelling of Liquid Phase Adsorption of Methylene Blue onto Moringa Pod Husk Activated Carbon

Abstract: This study focused on the liquid phase sorption of methylene blue (MB) using low cost agro-waste from moringa pod husks. Moringa pod husk was carbonized at 450°C for 30 min, which was later activated with 0.1 M phosphoric acid. The physico-chemical properties of moringa pod activated carbon (AMP) were determined. The results of the physicochemical parameters are: moisture content (13.6 ± 0.02), ash content (2.61 ± 0.11), point of zero charge (pH ZPC) (7.2) and bulk density (0.6 g L-1). The sample was also char… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
9
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 20 publications
3
9
0
Order By: Relevance
“…For the removal of Diuron, the value of the activation enthalpy (Δ H °) is <40 kJ/mol, which allows us to suggest that the uptake process follows a physisorption mechanism (de Bezerra et al 2020 ). The same behavior was observed in Adebayo et al ( 2019 ). The authors observed the increase in the randomness degree during the adsorption process, which confirmed the physisorption nature of the sorption mechanisms (Adebayo et al 2019 ).…”
Section: Effect Of Operational Parameters In Biosorption By ...supporting
confidence: 88%
See 4 more Smart Citations
“…For the removal of Diuron, the value of the activation enthalpy (Δ H °) is <40 kJ/mol, which allows us to suggest that the uptake process follows a physisorption mechanism (de Bezerra et al 2020 ). The same behavior was observed in Adebayo et al ( 2019 ). The authors observed the increase in the randomness degree during the adsorption process, which confirmed the physisorption nature of the sorption mechanisms (Adebayo et al 2019 ).…”
Section: Effect Of Operational Parameters In Biosorption By ...supporting
confidence: 88%
“…The same behavior was observed in Adebayo et al ( 2019 ). The authors observed the increase in the randomness degree during the adsorption process, which confirmed the physisorption nature of the sorption mechanisms (Adebayo et al 2019 ). A decrease in the percentage removal of Cr(IV) from 91.40 to 37.93% using Moringa stenopetala seed powder (MSSP) has been observed as temperature increased from 293 to 353 K. Similar observation has been made on adsorption capacities of Cr(VI) ion when the adsorption capacity of MSSP for Cr(VI) was decreased from 1.37 to 0.57 mg/g with increasing temperature from 293 to 353 K. This fall of the adsorbent metal uptake capacity with an increase in temperature might be due to desorption caused by an increase in the available thermal energy.…”
Section: Effect Of Operational Parameters In Biosorption By ...supporting
confidence: 88%
See 3 more Smart Citations